Case Report: Metastatic benign fibrous histiocytoma: a case series and review of diagnostic and therapeutic challenge - Liu, Xuesi; Sun, Zhengwang; Wu, Huajian; Ye, Qingrong; Wang, Chunmeng; Sun, Yangbai; Yan, Wangjun (Frontiers in Oncology, 2025)
BackgroundBenign Fibrous Histiocytoma (BFH), also known as dermatofibroma, is a common benign mesenchymal tumor of the skin. Although typically non-aggressive, rare cases of metastatic BFH pose diagnostic and therapeutic challenges.MethodsThis study reviews 10 cases of metastatic BFH diagnosed at Fudan University Shanghai Cancer Center between 2009 and 2024, with a detailed examination of three cases involving recurrent and metastatic behavior. Immunohistochemical markers and radiological imaging findings were analyzed to characterize tumor progression and treatment responses.ResultsThe cases highlighted distinct patterns of recurrence and metastasis, including lymphatic and distant organ involvement. Immunohistochemical analysis demonstrated variable expression of markers such as Vimentin, CD68, CD163, Ki67, and SMA.ConclusionsMetastatic BFH remains a rare but clinically significant condition. Early recognition, accurate histopathological diagnosis, and multimodal therapies are crucial for effective management.